1983
DOI: 10.1007/bf00427496
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, affect, and the disinhibition of verbal behavior

Abstract: A study was conducted to investigate the effects of acute alcohol administration on affective states and verbal behavior during the ascending and descending limbs of the blood alcohol curve. Sixteen male social drinkers were given alcohol (1.0 g/kg) or placebo in a double-blind crossover research design. Subjects tested while blood alcohol levels (BAL) were ascending close to peak concentration (0.11 g%) described themselves as more elated, friendly, and vigorous than when tested under placebo conditions. As B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
59
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(67 citation statements)
references
References 17 publications
8
59
0
Order By: Relevance
“…Rohrberg and SousaPoza [149] reported that social communication was affected at a BAL of 0.05% but no increase in talkativeness was found. Babor et al [150] reported an increase in verbosity at high BAL (0.1%), but no measurements were made of inhibitions or expectations. Lindfors and Lindman [151] studied the effect of alcohol on interactions in groups of 4 subjects, 2 men and 2 women.…”
Section: Verbal Behaviormentioning
confidence: 99%
“…Rohrberg and SousaPoza [149] reported that social communication was affected at a BAL of 0.05% but no increase in talkativeness was found. Babor et al [150] reported an increase in verbosity at high BAL (0.1%), but no measurements were made of inhibitions or expectations. Lindfors and Lindman [151] studied the effect of alcohol on interactions in groups of 4 subjects, 2 men and 2 women.…”
Section: Verbal Behaviormentioning
confidence: 99%
“…The acute effects of ethanol are biphasic: at lower internal concentrations, ethanol acts as a stimulant, whereas, at higher concentrations, it acts as a depressant (1). The stimulant effects of ethanol manifest as elevated mood and energy level in humans and as increased locomotor activity in animal models, and are thought to reflect the reinforcing properties of ethanol (2,3). In contrast, the depressant effects of ethanol manifest in humans as depressed mood, fatigue, and cognitive and motor impairment (2,4); animal models similarly exhibit motor incoordination and ultimately sedation (1).…”
mentioning
confidence: 99%
“…The stimulant effects of ethanol manifest as elevated mood and energy level in humans and as increased locomotor activity in animal models, and are thought to reflect the reinforcing properties of ethanol (2,3). In contrast, the depressant effects of ethanol manifest in humans as depressed mood, fatigue, and cognitive and motor impairment (2,4); animal models similarly exhibit motor incoordination and ultimately sedation (1). Several studies have suggested that susceptibility to alcohol use disorders (AUDs) is correlated with increased sensitivity to the stimulant effects of ethanol and decreased sensitivity to its depressant effects (5,6).…”
mentioning
confidence: 99%
“…The wing, being one of the distinctly viewed phenotype, is an ectodermal structure with well-defined compartmentalization of the wing contents and portions into two distinct groups of boundary classifications; one being anterior-posterior and the other being dorsal-ventral (Acheson et al, 1998;Ashburner, 1998;Babor et al, 1983). The dorsal and ventral epithelial sheets are considered to superimpose on each other, to form what we see as an ectodermal wing blade in its mature form.…”
Section: Introductionmentioning
confidence: 99%